Uterine Carcinomas in Tetrabromobisphenol A-Exposed Wistar Han Rats Harbor Increased Tp53 Mutations and Mimic High-Grade Type I Endometrial Carcinomas in Women - Harvey, Janice B. (Toxicol Pathol, 2015)
Endometrial carcinoma is the most common gynecologic malignancy is the United States, and accounts for 6% of all cancers in women. The disease is classified as Type I or Type II based on clinicopathologic and molecular features. It is a multifactorial disease with a number of risk factors, including environmental exposures. How environmental exposures, such as flame retardants, may affect the incidence of endometrial cancer is a topic of current and ongoing interest. Tetrabromobisphenol A (TBBPA) is a widely used brominated flame retardant found in a variety of household products. A recent two-year National Toxicology Program carcinogenicity study found that exposure to TBBPA was associated with a marked increase in the development of uterine tumors, specifically uterine carcinomas, in Wistar Han rats. Molecularly, TBBPA-induced uterine carcinomas in Wistar Han rats were characterized by a marked increase in Tp53 mutation compared to spontaneous uterine carcinomas, as well as overexpression of Her2. Similar to spontaneous carcinomas, tumors in TBBPA-exposed rats were ERα positive and PR negative by immunohistochemistry. The morphologic and molecular features of uterine carcinomas in TBBPA-exposed rats resemble those of high-grade Type I tumors in women, and these data suggest that exposure to TBBPA may pose an increased cancer risk.